Study on the Influencing factors of urban economic resilience in post epidemic Era: A case study of Kunming City - Hao Wang; Yan Li; Yuzi Liu; Fengling Qing; Yidian Zhou; Youming Chen; Dandan Fang (Journal of Urban Management, 2021)
At the end of 2019, the outbreak of the COVID-19 has a huge impact on China and the world economy, highlighting the vulnerability of the economy in the face of major shocks. The capability to resist pressure and risk of economic resilience can significantly improve the capability of the economy to resist external interference and recover its development. Kunming is located in the "Belt and Road" Economic Zone and is a bridgehead that radiates South Asia and Southeast Asia. Its economic development is particularly affected by the epidemic. How to improve the resilience of the regional economy will be of great strategic significance to achieve high-quality economic development. Taking Kunming as an example, this paper identifies the influencing factors of regional economic development through literature research and expert interviews and constructs a hypothesis model of influencing factors of economic resilience. From the three dimensions of "defense, absorption and learning" of resilience theory, data are collected through questionnaires, and the mechanism between resilience theory and economic development is explored by using the structural equation model(SEM). According to the main factors identified by the model, the paper figures out countermeasures to prompt the development of the regional economic better and faster.
Keywords: 710; COVID-19; Economic resilience; Influencing factors; Structural equation model(SEM)